2022
DOI: 10.3389/fendo.2022.972963
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes associated with HPV infection in women aged over 50 years: A cross-sectional study from China’s largest academic woman’s hospital

Abstract: BackgroundMetabolic disturbances and immune alterations caused by diabetes are not just bystanders of HPV infection, but the conclusion that diabetes increases the risk of HPV infection requires more clinical epidemiological evidence to confirm. Our aim was to evaluate the association of diabetes with HPV infection risk in female patients aged over 50 years in the cervical clinic.MethodsWe conducted a cross-sectional study of 6402 women aged over 50 years in the cervical clinic between May 2019 and March 2022 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It is thus clear that DM can result in metabolic characteristics and immune alterations that in turn trigger persistent hr-HPV infection, and is not a mere ‘bystander’ of hr-HPV infection [ 19 ]. Despite this, there is a paucity of epidemiological evidence to support the conclusion that DM promotes hr-HPV infection and few studies have reported on the potential link between DM and hr-HPV [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus clear that DM can result in metabolic characteristics and immune alterations that in turn trigger persistent hr-HPV infection, and is not a mere ‘bystander’ of hr-HPV infection [ 19 ]. Despite this, there is a paucity of epidemiological evidence to support the conclusion that DM promotes hr-HPV infection and few studies have reported on the potential link between DM and hr-HPV [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus clear that DM can result in metabolic characteristics and immune alterations that in turn trigger persistent hr-HPV infection, and is not a mere ‘bystander’ of hr-HPV infection [ 19 ]. Despite this, there is a paucity of epidemiological evidence to support the conclusion that DM promotes hr-HPV infection and few studies have reported on the potential link between DM and hr-HPV [ 19 ]. Again, the increasing prevalence of DM in Ghana [ 20 ] necessitates an understanding of whether women with DM are at an increased risk of hr-HPV infection, and therefore cervical precancerous lesions.…”
Section: Introductionmentioning
confidence: 99%